2009
DOI: 10.1021/es9013932
|View full text |Cite
|
Sign up to set email alerts
|

Biocorrosive Thermophilic Microbial Communities in Alaskan North Slope Oil Facilities

Abstract: Corrosion of metallic oilfield pipelines by microorganisms is a costly but poorly understood phenomenon, with standard treatment methods targeting mesophilic sulfatereducing bacteria. In assessing biocorrosion potential at an Alaskan North Slope oil field, we identified thermophilic hydrogen-using methanogens, syntrophic bacteria, peptideand amino acid-fermenting bacteria, iron reducers, sulfur/thiosulfate-reducing bacteria and sulfate-reducing archaea. These microbes can stimulate metal corrosion through prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(164 citation statements)
references
References 36 publications
5
157
2
Order By: Relevance
“…In alkyl-SS enzymes, the substitution of alanine for leucine directly adjacent to the presumed binding site of the substrate could make room for the terminal methyl group to shift away from the catalytic cysteine, thus allowing for hydrogen atom abstraction at C2. There have also been proposals of terminal hydrogen atom abstraction in short chain alkanes (40) and even the proposal that methane could be activated by an XSS (41). However, the ability of an alkyl-SS to perform such a dramatically uphill C-H bond cleavage (42) has not been substantiated in vitro to date, and no candidate XSS has been proposed for this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In alkyl-SS enzymes, the substitution of alanine for leucine directly adjacent to the presumed binding site of the substrate could make room for the terminal methyl group to shift away from the catalytic cysteine, thus allowing for hydrogen atom abstraction at C2. There have also been proposals of terminal hydrogen atom abstraction in short chain alkanes (40) and even the proposal that methane could be activated by an XSS (41). However, the ability of an alkyl-SS to perform such a dramatically uphill C-H bond cleavage (42) has not been substantiated in vitro to date, and no candidate XSS has been proposed for this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular techniques for community analysis is still rare in corrosion studies. Denaturing gradient gel electrophoresis (DGGE) on corroded iron and oil pipelines (Bermont-Bouis et al, 2007;Duncan et al, 2009;Oliveira et al, 2011;Cote et al, 2014;Marty et al, 2014) showed that the microbial communities involved in corrosion are much more complex than was found so far with culturing methods. Standard metal biocorrosion-monitoring procedures focus mainly on SRB detection, and although SRB are also found in many molecular studies they are not always the most abundant or most relevant microorganisms.…”
Section: Perspectivesmentioning
confidence: 99%
“…Strain OS1 T was the dominant culturable heterotroph, present in the production water at 2.3 cells ml 21 (MPN). The dominant culturable hydrogen oxidizer, Methanothermobacter thermautotrophicus, was present at the same cell density (Duncan et al, 2009). The Hungate agar roll-tube method was used for isolation (Hungate, 1969).…”
Section: Strain Os1mentioning
confidence: 99%